STUDY THE BIOCHEMICL EFFECT OF GUM ARABIC IN LIVER INJURY AND BLOOD SERUM OF MICE INDUCE BY GENTAMICIN - Ghassan F. Alubaidy (Basrah Journal of Veterinary Research)
Forty adult male Bulb/c mice weighing between 25-30 GM reared in wire cages were randomly divided into four groups (10 mice each group). Group (G1) received the regular mice diet and (1 ml/kg Saline p.o.) for 8 days maintained as a control group. Group (G2) treated daily intra peritoneal (i.p) injection of gentamicin (40m g/kg bwt /day) for 8 days. In group (G3) received Gum Arabic (GA) (10 gm /kg bwt /day) for 8 days orally by using stomach tube. Group (G4) is received gentamicin (40 mg/ kg bwt /day) (i.p) plus (10gm /kg bwt / day) orally of Gum Arabic for 8 days. Blood samples were collected after overnight fasting 12-24 hours for determination some biochemical marker including AST, ALT and ALP activities, creatinin, uric acid , urea and total bilirubin in serum . Assay the total protein, Deoxyribonucleic acid DNA, ribonucleic acid RNA in liver tissue of mice. The results revealed that treatment with gentamicin (G2) increased in AST, ALT and ALP activities in serum, creatinine, uric acid, urea and total bilirubin value in serum also there are elevation the level of DNA, RNA and total protein in liver tissue when a compared with the control group (G1).Treatment of GA along with gentamicin (G4) and administration of GA alone (G3) decreased in the level of serum creatinine, serum uric acid, serum urea and serum total bilirubin , the level of DNA, RNA and total protein in liver tissue also decrease, as compared to the gentamicin treated group (G2) but not reach in both groups(G3,G4) to normal level as in control group. In conclusion Gum Arabic exhibit hepatoprotective activities probably through free radical scavenging properties. Altered level of hepatic markers such as AST, ALT, and ALP with gentamicin exposure was reversed towards normalization with Gum Arabic. Similarly, biochemical parameters were also restored by Gum Arabic. Bioactive of Gum Arabic ameliorated the oxidative damage and had increased the regenerative and reparative capacity of liver.